2014
DOI: 10.1016/j.proeng.2014.10.537
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in Energy and Environmental Design (LEED) and its Impact on Building Operational Expenditures

Abstract: Histidine phosphorylation plays a key role in prokaryotic signaling and accounts for approximately 6% of the protein phosphorylation events in eukaryotics. Phosphohistidines generally act as intermediates in the transfer of phosphate groups from donor to acceptor molecules. Examples include the bacterial phosphoenolpyruvate:sugar phosphotransferase system (PTS) and the histidine kinases found in two-component signal transduction pathways. The latter are utilized by bacteria and plants to sense and adapt to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…Numerous studies have reported the positive influence of ISO 14001 on environmental performance (Arimura, Hibiki, & Katayama, ; Arimura, Darnall, Ganguli, & Katayama, ; Dasgupta, Hettige, & Wheeler, ; Johnstone, Serraville, Scapecchi, & Labonne, ; Potoski & Prakash, ). Similarly, energy and water savings are achieved in LEED certified buildings (Dobiáš & Macek, ). Finally, environmental awards, which are based on thorough assessment by industry and experts, are signals of positive corporate environmental performance (Klassen & McLaughlin, ).…”
Section: Methodsmentioning
confidence: 98%
“…Numerous studies have reported the positive influence of ISO 14001 on environmental performance (Arimura, Hibiki, & Katayama, ; Arimura, Darnall, Ganguli, & Katayama, ; Dasgupta, Hettige, & Wheeler, ; Johnstone, Serraville, Scapecchi, & Labonne, ; Potoski & Prakash, ). Similarly, energy and water savings are achieved in LEED certified buildings (Dobiáš & Macek, ). Finally, environmental awards, which are based on thorough assessment by industry and experts, are signals of positive corporate environmental performance (Klassen & McLaughlin, ).…”
Section: Methodsmentioning
confidence: 98%
“…This paper uses 1-year timeseries data of a Platinum LEED ENERGY STAR 99/100, Net Zero-certified building in the Houston, TX area [21]. From the building design, construction, and management perspectives, the LEED standards were developed in 1993 to build highly efficient and green buildings that are comfortable and healthy for occupants.…”
Section: Introductionmentioning
confidence: 99%
“…[20] ve své studii, kde se zaměřili na hodnocení tepelně izolačních vlastností vegetativních střech, aby poukázali na to, že zelené střechy fungují jako izolační vrstva pro budovy. Z jejich studie vyplývá, že zelené střechy mohou ušetřit od 1, Široká paleta výhod spojených se zelenými střechami, zejména jejich potenciál snižovat energetické požadavky na vytápění a chlazení, dala podnět k tomu, aby i jeden z nejuznávanějších systémů certifikace udržitelnosti budov LEED [21] podporoval zelenou infrastrukturu. Při instalaci vegetačního souvrství je možné získat až 34 bodů ze 110 potřebných k obdržení nejvyšší Platinové certifikace.…”
Section: úSpora Energieunclassified